Analysis of the Role of Artificial Intelligence-Based Personalization Marketing on Customer Satisfaction and Repurchase Intention in the E-Commerce Industry in Indonesia - Putri Pratiwi; Suwardi (Universitas Sains dan Teknologi Komputer, 2026)
The rapid development of digital technology has encouraged e-commerce platforms to adopt Artificial Intelligence (AI)-based personalization marketing to enhance customer experience and maintain competitiveness. This study aims to analyze the role of AI-based personalization marketing on customer satisfaction and its impact on repurchase intention in the Indonesian e-commerce industry. A quantitative approach with an explanatory research design was employed, using primary data collected through an online questionnaire from 200 respondents who have experience with personalized recommendations on e-commerce platforms, and analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS). The findings indicate that AI-based personalization marketing significantly influences customer satisfaction, which in turn has a positive effect on repurchase intention, while also acting as a mediating variable between the two constructs. These results suggest that effective personalization strategies can enhance consumer satisfaction and strengthen long-term purchasing behavior. This study contributes to the literature by providing empirical evidence in the Indonesian context and offers practical implications for e-commerce practitioners in optimizing AI-driven marketing strategies.